Efficacy of ozone gas as disinfecting pre-treatment to minimise pathogen transmission through food packaging - Tay, Hui Ling (Nanyang Technological University, 2021)
Global food supply chains of today allow us to enjoy food from every corner of the world. However, with the growing scale and increasing complexity of the global food supply chain, ensuring food safety is growingly difficult. This system that we depend on for the speedy transport of food supplies is increasingly vulnerable to falling host and playing vector to infectious disease outbreaks. During Covid 19, food safety management systems cannot afford to have vulnerabilities. One such vulnerability identified in this study is the neglect of food packaging as a vector for virus transmission. To minimise this risk, a disinfection pre-treatment by ozone gas is considered. In this study, the effectiveness of using ozone gas as a surface disinfectant to minimise pathogen spread via food packaging is investigated by applying ozone gas on a packaging film with a contaminant. The bacteria used is laboratory-grown E. coli. Experiments using 6 different ozone concentrations ranging from 0ppm to 3ppm under 5 different exposure timings ranging from1min, to 15 min were conducted to inactivate 0.1OD of E-Coli from 2 different stages of bacterial growth (Exponential Growth Stage and Stationary Growth Stage) to determine the trends in inactivation efficiency of ozone on E. Coli and evaluate the material compatibility of ozone with LDPE plastic packaging. It was found that the inactivation efficiency of ozone increase with ozone concentration and that exponential phase E coli are generally more vulnerable to ozone disinfection than stationary phase E. coli. Also, ozone was shown to cause small degree of deformation on LDPE. These results lend support to the idea that single application of ozone pre-treatment is suitable for food packaging surfaces, especially if disinfection treatment is employed within the exponential phase of the bacteria.